Synthesis and characterization of lead-free 0.5Ba(Zr0.2Ti0.8)O-3-0.5(Ba0.7Ca0.3)TiO3 ceramic - Coondoo, Indrani (2013)
Polycrystalline sample of lead-free 0.5Ba(Zr0.2Ti0.8)O-3-0.5(Ba0.7Ca0.3)TiO3 ceramic has been synthesized by solid state reaction method. Single-phase perovskite structure with rhombohedral symmetry was confirmed by x-ray diffraction. Temperature dependent dielectric permittivity studies demonstrated frequency independent behavior, indicating that the studied sample was not a typical relaxor ferroelectric. A polymorphic phase transition between rhombohedral and tetragonal phase was noticed near room temperature followed by a tetragonal to cubic transition with 97 degrees C as the temperature of maximum permittivity. The macroscopic values of d(33) and d(31) were similar to 350 pC/N and -141 pm/V, whereas the electromechanical coupling factors k(p) and k(t) were 44.5% and 41.6%, respectively. Bulk P-E hysteresis loop was obtained with saturation polarization 11 mu C/cm(2) and coercive field similar to 4 kV/cm. Distinct polarization contrast with a complex mosaic-like domain structure was observed in the out-of-plane mode of piezoresponse force microscopy. The domain width and the correlation length were estimated to be nearly 2 mu m and 827 nm, respectively. Local hysteresis loop with apparent coercive voltage, V-c = 15.8 V, was observed. (C) 2013 AIP Publishing LLC.